Clinico-epidemiological Characteristics of Acute Covid-19 Patients in a Tertiary Care Hospital of Dhaka, Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: The COVID-19 pandemic is a catastrophe enormously affecting the whole world including Bangladesh. This disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) began in Wuhan, China, in December 2019, and since then has been spreading globally. Objectives: To find out the sociodemographic, clinical characteristics and in-hospital outcome of patients of acute COVID-19 confirmed cases in a tertiary care hospital. Methodology: It was a hospital based observational study. Consecutive samples were taken from RT-PCR positive cases (ranging from mild to severe form) admitted in COVID-19 unit of Shaheed Suhrawardy Medical College Hospital, Dhaka during the period of July 1st to August 31st 2020. Socio-demographic and clinical data were collected by using a pretested structured questionnaire. The severity of the COVID- cases was assessed based on the WHO interim guideline. Analysis was done with SPSS (Statistical Package for Social Science) version-23.Results: Total 77 cases were found valid for study according to inclusion and exclusion criteria. Male patients were predominant which was 72.7%. Mean age was found 53.32±13.48 years. The mean age was significantly higher (58.82±11.74 years) in severe group. Fever, shortness of breath (SOB), cough and body ache were the most common presenting symptoms. Body ache was significantly higher in mild & moderate group than severe group. SOB and sore throat were significantly higher in severe group (53.5% vs 79.4%) and (9.3% vs 26.5%) respectively. Diabetes 29(37.7%), hypertension 18(23.4%), CKD 16(20.8%) and hypothyroidism 16(20.8%) were most frequent co-morbidities among the patients. Diabetes, CKD, hypothyroidism and COPD were significantly higher in severe group than mild & moderate group. The mean neutrophil lymphocyte ratio (NLR) was found 1.3±0.3 in mild & moderate group and 2.3±1.0 in severe group. Mean C-reactive protein was found 6.2±2.3 mg/L in mild & moderate group and 8.5±3.9 mg/L in severe group. The mean sodium was found 143.6±7.9 mEq/L in mild & moderate group and 136.5±9.8 mEq/L in severe group. The mean potassium was found 4.7±0.7 mEq/ L in mild & moderate group and 3.9±1.2 mEq/L in severe group. Where X-ray chest (CXR) could reveal abnormalities only in 8 cases (10.4%); HRCT-chest was able to find out abnormalities in 56 cases (72.7%). Abnormal HRCT chest was found in 56 patients among them 48(87.3%) showed normal finding on chest x-ray. The difference was statistically significant between two groups. In HRCT chest abnormalities ground glass opacities (GGOs) was the most frequent observation in 33(58.93%) patients. GGOs was found 12(50.0%) in mild & moderate group and 21(65.63%) in severe group. Major complications were pneumonia 39(50.6%) and severe pneumonia 28(36.4%) respectively. Pneumonia was significant higher in mild & moderate group than severe group (76.7% vs 17.6%). Severe pneumonia was observed 27(79.4%) in severe group. The above-mentioned parameters were statistically significant (p